Academic Institution Telecommunication Infrastructure Development - Antoniuk, Y.M. (Управляющие системы и машины, 2015)
The problem of the software choice and the hardware solutions, the creation principles and application services of the scientific and educational academic institutions environment in condition of the basic developing, the information communication technology innovation and general globalization is scrutinized. Based on the technological standards analysis that apply to the telecommunications infrastructure and network management centers, the recommendations for the network control center creation, in particular, the basic computer telecommunication center are described. Розглянуто задачу вибору програмно-технічних рішень, принципів створення і застосування сервісів науково-освітнього простору академічної установи в умовах розвитку базових і перспективних комунікаційних та інформаційних технологій і загальної глобалізації. На основі аналізу технологічних стандартів, які застосовуються в телекомунікаційних структурах і центрах управління мережами описано формування рекомендацій щодо створення центру управління мережами, зокрема, базового комп'ютерного телекомунікаційного вузла. Рассмотрена задача выбора программно-технических решений, принципов создания и применения сервисов научно-образовательного пространства академического учреждения в условиях развития базовых и перспективных коммуникационных и информационных технологий и общей глобализации. На основе анализа технологических стандартов, применяемых в телекоммуникационных структурах и центрах управления сетями, описано формирование рекомендаций по созданию центра управления сетями, в частности, базового компьютерного телекоммуникационного узла.